UNCONSECRATED BURIAL AND EXCOMMUNICATION IN ANGLO-SAXON ENGLAND: A REASSESSMENT. (2019) - MARAFIOTI, NICOLE
Abstract : This article investigates the ideologies which underpinned unconsecrated burial in late Anglo-Saxon legal and religious texts. The exclusion of sinners and criminals from Christian cemeteries has typically been interpreted by scholars as a form of excommunication or an attempt to facilitate damnation. However, a reassessment of legislative, diplomatic, and ecclesiastical sources reveals that this was not so. In tenth-century laws and charters, unconsecrated burial was imposed exclusively by secular authorities; it was only prescribed by ecclesiastical authorities from ca. 1000. This suggests that it originated as a temporal punishment but later came to be used as an ecclesiastical sentence. The following analysis of the textual evidence yields two interrelated arguments. First, this article demonstrates that through the mid-eleventh century, unconsecrated burial was a penalty distinct from ecclesiastical excommunication. Where excommunication was imposed upon living sinners, to coerce them to penance, unconsecrated burial was prescribed for the unrepentant or criminal dead, whose actions placed them beyond earthly help. Second, this article contends that written prescriptions for unconsecrated burial differentiated secular from ecclesiastical jurisdictions. Although laymen and clergy collaborated in the dispensation of law and justice throughout the Anglo-Saxon period, the written evidence for unconsecrated burial shows that this penalty fell either under the authority of secular or of ecclesiastical agents, demonstrating a clearer separation between these spheres than is usually recognized in pre-Conquest England.